2009
DOI: 10.1007/978-3-642-00224-3_5
|View full text |Cite
|
Sign up to set email alerts
|

A Context and Content-Based Routing Protocol for Mobile Sensor Networks

Abstract: The need of monitoring people, animals, and things in general, brings to consider mobile WSNs besides traditional, fixed ones. Moreover, several advanced scenarios, like those including actuators, involve multiple sinks . Mobility and multiple sinks radically changes the way routing is performed, while the peculiarities of WSNs make it difficult to reuse protocols designed for other types of mobile networks.\ud \ud In this paper, we describe CCBR, a Context and Content-Based Routing Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Otherwise, it will update the distance in the header and schedule the packet for transmission. The results in [45] show that CCBR's delivery rate is good and the routing cost is low. Another technique for event routing has been proposed in [46].…”
Section: Event-based Routingmentioning
confidence: 97%
See 1 more Smart Citation
“…Otherwise, it will update the distance in the header and schedule the packet for transmission. The results in [45] show that CCBR's delivery rate is good and the routing cost is low. Another technique for event routing has been proposed in [46].…”
Section: Event-based Routingmentioning
confidence: 97%
“…The key feature of Kyra is its ability to balance the routing load over the sub-servers. The authors of [45] proposed the Context and Content-Based Routing Protocol (CCBR) for multi-sink mobile wireless sensor networks. It capitalizes on the broadcast feature of wireless networks.…”
Section: Event-based Routingmentioning
confidence: 99%
“…Others have exhibited framework systems in view of context data, e.g. evaluating and anticipating remote system conditions [10], system steering [35], battery administration [8], [36], and energy proficient GPS obligation cycling [12], [13]. Further, Eagle and Pentland have demonstrated that gadget use examples are in reality organized and unsurprising [37].…”
Section: Literature Surveymentioning
confidence: 99%
“…[6] Especially in arrangement with mobile devices these methods are used to increase necessity extremely. Highly dynamic computing setting like ubiquitous and pervasive computing, involve regular adaptation of applications.…”
Section: Context Aware Strategymentioning
confidence: 99%